IMPLEMENTATION OF THE INSAN BERINOVASI PROGRAM AN EFFORT TO IMPROVE PARTICIPATION IN SOCIAL SECURITY ADMINISTRATOR FOR EMPLOYMENT - Aprilia, Annisa Zahra; Ivan, Darmawan; Afrilia, Ufa Anita (Jurnal Governansi, 2026)
Social security administrator for employment created the Insan Berinovasi program as an innovation in improving the quality and public services to participants of the social security workforce. The phenomenon that occurs is that obstacles in the process will be faced by the government and implementers of the social security workforce in the current period, namely to increase the number of social security participants themselves because social security workforce in Indonesia is still not evenly distributed. The purpose of this study is to determine the implementation and procedures for creating the Insan Berinovasi program at BPJS Ketenagakerjaan, as well as to identify the planning strategies implemented for the Insan Berinovasi program from year to year. In addition, to describe the factors that influence the implementation of this Insan Berinovasi program. The research method used is descriptive qualitative, with a performance report approach based on direct observation and experience during internship activities at BPJS Ketenagakerjaan Management System Management Division Deputy Strategic Planning. The results of the study indicate that the implementation of this Insan Berinovasi program has been running quite well according to plan, but there are obstacles in the timeliness of implementation. Therefore, the planning of this Insan Berinovasi program needs to be optimized in order to have maximum results. The conclusion of this research is that the Insan Berinovasi program has a positive impact on institutions and also the community because it addresses problems that exist in the BPJS Employment environment and in the community.